Bentall procedure after Ross surgery - Sitar, L. L.; Zhekov, I. I.; Osadovska, I. A.; Perepeluyk, A. I.; Khyzhniak, K. A.; Zinchenko, H. A.; Vayda, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2017)
Summary. Describes the advantages and disadvantages of surgical treatment before, during and after surgery in two patients. Purpose. To provide positive results performing Bentall operation after previous Ross surgery. Materials and Meth-ods. Our article presents two clinical cases performing Bentall operation after previous Ross surgery. Results and discussion. According to our experience it shows dilatation of the valve ring and expansion of the sinuses of Valsalva in late postopera-tive period, that confirms literature data and our clinical experience. Conclusions. The disadvantage of Ross procedure is considered to be very high invasiveness interference with aortic valve transplant, that requires additional replacement of pulmonary valve. Changes in both valves often occur as a complication in the postoperative period leading to the re-surgery. The postoperative period presented in two cases proceeded without complications, both patients were discharged in satisfac-tory condition.